Necromass in forests of Madre de Dios, Peru: a comparison between terra firme and lowland forests - Araujo-Murakami, Alejandro (2011)
Stocks of dead wood or necromass represent an important portion of biomass and nutrients in tropical forests. The objectives of this study were: 1) to evaluate and compare the necromass of “terra firme” and lowlands forests, (2) to study the relationship between necromass, above-ground biomass and wood density, and (3) to estimate the necromass of the department of Madre de Dios, Peru. Stocks of necromass and above-ground biomass were estimated at three different locations using permanent plots and line intercept transects. The average volume of necromass for the three sites was 72.9 m3 ha-1 with an average weight varying between 24.8 and 30.7 Mg ha-1, depending on the estimations of dead wood density used for the calculations. Terra firme forests had significantly higher stocks of necromass than lowland forests. The amount of necromass was 11% of the total above-ground biomass in Madre de Dios forests. The total stock of carbon stored in dead wood for the entire department of Madre de Dios was estimated to be approximately 100 mega tonnes of carbon. This is ten times more than the annual fossil fuel emissions of Peru between 2000 and 2008. The substantial stocks of necromass emphasize the importance of these types of field studies, considering that this component of tropical forest carbon cannot be detected using other methods such as satellite remote sensing.